MICRO FINANCE IN THE EMPLOYMENT GENERATION AMONG THE RURAL SECTOR IN BIHAR - MICKY KUMARI (International Journal of Multidisciplinary Research and Studies, 2020)
Additionally, it backed grassroots movements in Khagaria and Nawada's struggles. Their help extended to the early childhood care and education programmes, which were of great importance to the overall education and growth of the children who participated. By the year 1996, NIDAN had began extending loans to organisations, with a major emphasis on the provision of financial assistance to women's populations. Bandhan is one of the numerous models that have been implemented as part of the purview of microfinance banks. microfinance organisations were designed to empower women by providing them with rapid loans; nevertheless, the microfinance institutions ended up reversing the social and economic gains, and the women who received these loans ended up becoming slaves. The burgeoning microlending sector in India is a part of a worldwide phenomena that originated as a philanthropic movement but now now draws private money looking for development. This shift in focus from charitable organisations to private investors is driving the industry's expansion.